Information processes, stimulation and perceptual training in fencing - Borysiuk, Z.; Waskiewicz, Z. (Journal of Human Kinetics, 2008)
Learning and development of motor skills and techniques in fencing and other sports with open motor habits are based on perceptual processes involving the senses of vision, touch, and hearing. In fencing, the same stimuli can yield defensive or offensive actions, which are strictly related to the tactics and strategy. Different types of stimulation determine reaction time, movement time, and muscle bioelectric tension (EMG) in fencing. From the training process, controlling the significance of dominant stimuli should be taken into account. The results of presented studies of advanced and novice fencers show that the time of reaction to tactile stimulation is similar or slightly shorter than to acoustic stimuli followed by visual stimuli. The advanced fencers were faster than the novice fencers in all the studied parameters. The EMG signal was significantly lower in case of advanced fencers in all three types of stimulation. This indicates that the psycho-motor superiority of elite fencers results in a reduction of the bioelectrical tension of muscles involved in performing the motor tasks. Perceptual skills enable athletes to respond to important signals in sport competition and ignore disrupting ones which lower the effectiveness of sports combat. Time pressure during sports competition makes it necessary to reduce as much as possible the decision-making time and the time of sensorimotor responses in the motor phase. The results show that experienced athletes make decisions much faster than their novice colleagues. It conforms to the main strategy of perceptual training, (i.e., gaining maximum benefits at the lowest expense). Speed of decision-making is strictly associated with the stimuli detection effectiveness and re-creation of acquired motor patterns.